Pengaruh Fasilitas Kerja, Beban Kerja, dan Lingkungan Kerja Fisik terhadap Produktivitas Kerja Pegawai Sekretariat DPRD Pemerintah Kabupaten Kediri - Dielta Windiasyunar; Aprilia Dian Evasari; Endah Kurniawati (Yayasan Literasi Sains Indonesia, 2026)
This study aims to explain and demonstrate the influence of work facilities, workload, and the physical work environment on the work productivity of employees at the Secretariat of the Regional People’s Representative Council (DPRD) of Kediri Regency. This study employs a quantitative approach, with data collected through purposive sampling involving 39 employees from the Secretariat of the Regional People’s Representative Council (DPRD) of Kediri Regency. The data were analyzed using validity tests, reliability tests, normality tests, multicollinearity tests, linearity tests, heteroscedasticity tests, multiple linear regression analysis, the t-test (partial), the F-test (simultaneous), and the coefficient of determination. Based on the results of the study, partially, work facilities have a positive and significant effect on the work productivity of employees at the Secretariat of the DPRD of Kediri Regency Government with a significance value of 0.000 < 0.05. Workload has a positive and significant effect on the work productivity of employees at the Secretariat of the DPRD of Kediri Regency Government with a significance value of 0.007 < 0.05. Physical work environment has a positive and significant effect on the work productivity of employees at the Secretariat of the DPRD of Kediri Regency Government with a significance value of 0.000 < 0.05. Simultaneously, work facilities, workload, and physical work environment have a positive and significant effect on the work productivity of employees at the Secretariat of the DPRD of Kediri Regency Government with a significance value of 0.000 < 0.05.